INTEGRATION OF INCLUSIVE EDUCATION AND INCLUSIVE TOURISM FOR LOCAL ECONOMIC EMPOWERMENT IN GEDEPANGRANGO TOURISM VILLAGE, SUKABUMI - Meitolo Hulu (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study examines the integration of inclusive education and inclusive tourism in Gedepangrango Tourism Village, Sukabumi, with the aim of reducing socio-economic disparities and supporting sustainable community development. Gedepangrango, which has a rich cultural and natural heritage, has the potential to develop inclusive tourism, but faces challenges in accessibility for the community, both in terms of infrastructure and educational facilities. This study aims to analyze how inclusive education can improve access to education for all groups, and how the synergy between inclusive education and inclusive tourism can support local economic empowerment. Additionally, this study identifies major barriers such as limited resources, infrastructure, and public awareness. Using a qualitative case study approach, data were collected through in-depth interviews, focus group discussions, participatory observation, and document analysis. The results show that although initial steps towards the implementation of inclusive education and tourism have been taken, further development of more accessible infrastructure and increased public awareness are crucial. This study recommends enhanced training for educators, the construction of more disability-friendly infrastructure, and a more inclusive approach to tourism in order to reduce social disparities and strengthen long-term economic resilience in Gedepangrango.